Cargoes in motion : materiality and connectivity across the Indian Ocean - Schnepel, Burkhard; Verne, Julia (Cultural geographer) (Indian Ocean studies series., 2022)
"Cargoes in Motion considers both the materiality and special trajectories of cargoes across the Indian Ocean world in order to better understand the processes of exchange and their economic, social, cultural, and political effects on the region"--